RESULT-ORIENTED STATE SUPPORT FOR CIVIL SOCIETY INSTITUTIONS: FINANCIAL TRANSPARENCY AND ACCOUNTABILITY ISSUES (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
In the contemporary system of public governance, civil society institutions perform an important mediating function between the state, communities and vulnerable social groups. Their participation in social protection, education, health, ecology, youth policy and local development makes public policy more inclusive and responsive. However, the real contribution of civil society institutions depends not only on the amount of public funding allocated to them, but also on how clearly this funding is connected with social results, financial discipline and public accountability.